1966
DOI: 10.1079/bjn19660021
|View full text |Cite
|
Sign up to set email alerts
|

Rumen development in the calf

Abstract: 1. Thirty Ayrshire bull calves were used in an experiment to study the effects of diets containing different proportions of concentrates to hay on rumen development at 12 weeks of age. In addition, six milk-fed calves were slaughtered at 3 weeks of age for comparison. 2. Restriction of the maximum daily allowance of concentrates to the lower levels was accompanied by an increase in the voluntary intake of hay, but the performance of calves from 3 to 12 weeks of age was significantly better in calves given the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(35 citation statements)
references
References 16 publications
2
32
0
1
Order By: Relevance
“…Blood BHBA is a measure of rumen epithelial metabolic activity, and it indicates the conversion of ruminal butyrate to circulating BHBA when it passes the rumen wall (Lane, Baldwin, & Jesse, 2000). In addition, ruminal fermentation of calf starter increases ruminal concentration of volatile fatty acids (VFA), especially of propionate and butyrate (Stobo, Roy, & Gaston, 1966;Warner, Flatt, & Loosli, 1956). In the present study, a time effect was observed for serum BHBA concentration (p < 0.01; Figure 3b), and regardless of dietary treatment, BHBA increased from 5 weeks after birth, similar to the fluctuation of starter DMI.…”
Section: Blood Igf-1 Glp-2 and Metabolitementioning
confidence: 99%
“…Blood BHBA is a measure of rumen epithelial metabolic activity, and it indicates the conversion of ruminal butyrate to circulating BHBA when it passes the rumen wall (Lane, Baldwin, & Jesse, 2000). In addition, ruminal fermentation of calf starter increases ruminal concentration of volatile fatty acids (VFA), especially of propionate and butyrate (Stobo, Roy, & Gaston, 1966;Warner, Flatt, & Loosli, 1956). In the present study, a time effect was observed for serum BHBA concentration (p < 0.01; Figure 3b), and regardless of dietary treatment, BHBA increased from 5 weeks after birth, similar to the fluctuation of starter DMI.…”
Section: Blood Igf-1 Glp-2 and Metabolitementioning
confidence: 99%
“…This development depends on the establishment of ruminal flora, initiation of feed consumption, absorption processes and absorption mechanisms [82]. The VFAs especially butyrate are important in triggering rumen papillae growth [83] which provide the surface area for absorption of nutrients. Recently researchers have demonstrated the importance of introducing starter in calves at an early age.…”
Section: Effects Of Scy On Gastrointestinal Parametersmentioning
confidence: 99%
“…The majority of liquid feed bypasses the reticulo-rumen by means of the oesophageal groove, and goes directly through the omasum to the abomasum (Church, 1969). The rumen mucosa exhibits only small and undeveloped papillae in milk-fed young ruminants (Warner & Flatt, 1965;Stobo et al 1966;Church, 1969). Therefore, a rather low estimate of FSR could be expected in the reticulo-rumen (Table 3).…”
Section: Measurements Of Protein Synthesismentioning
confidence: 99%